The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5935/0004-2749.20170041
|View full text |Cite
|
Sign up to set email alerts
|

The reasons for evisceration after penetrating keratoplasty between 1995 and 2015

Abstract: Although keratoplasty is one of the most successful types of surgery among tissue transplantations, our findings show that it is associated with a possible risk of evisceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…reviewed 16 cases of post-PKP evisceration and found that the most common cause was endophthalmitis (56.25%), followed by corneal melting (25%) and trauma (18.75%). [ 7 ] We suspected that the causes of severe orbital content prolapse in our case were multiple PKP surgeries, graft failure with marked cornea thinning, and sudden increase of abdominal pressure due to a severe cough.…”
Section: Discussionmentioning
confidence: 98%
“…reviewed 16 cases of post-PKP evisceration and found that the most common cause was endophthalmitis (56.25%), followed by corneal melting (25%) and trauma (18.75%). [ 7 ] We suspected that the causes of severe orbital content prolapse in our case were multiple PKP surgeries, graft failure with marked cornea thinning, and sudden increase of abdominal pressure due to a severe cough.…”
Section: Discussionmentioning
confidence: 98%